2020
DOI: 10.1182/blood.2020005064
|View full text |Cite
|
Sign up to set email alerts
|

Effects of germline DHFR and FPGS variants on methotrexate metabolism and relapse of leukemia

Abstract: Methotrexate (MTX) during maintenance therapy is essential to cure acute lymphoblastic leukemia (ALL), but dosing strategies to achieve adequate treatment intensity are challenged by inter-individual differences in drug disposition. To evaluate genetic factors associated with MTX metabolism, we performed a genome-wide association study in 447 ALL cases from the Nordic Society for Paediatric Haematology and Oncology ALL2008 study, validating results in an independent set of 196 patients. The intergenic SNP rs13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…For example, P-glycoprotein, which is a transmembrane efflux pump, can promote drug efflux in cancer cells, thus reducing the drug concentration in cancer cells and inducing multidrug resistance ( 43 ). Another example is that the intergenic single-nucleotide polymorphism of DHFR and FPGS could affect the levels of MTX in the serum, which results in inadequate treatment intensity and disease relapse after HD-MTX treatment in acute lymphoblastic leukemia patients ( 44 ). All patients included in the present cohort received HD-MTX-based chemoimmunotherapy, which is coincidentally an anti-metabolic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…For example, P-glycoprotein, which is a transmembrane efflux pump, can promote drug efflux in cancer cells, thus reducing the drug concentration in cancer cells and inducing multidrug resistance ( 43 ). Another example is that the intergenic single-nucleotide polymorphism of DHFR and FPGS could affect the levels of MTX in the serum, which results in inadequate treatment intensity and disease relapse after HD-MTX treatment in acute lymphoblastic leukemia patients ( 44 ). All patients included in the present cohort received HD-MTX-based chemoimmunotherapy, which is coincidentally an anti-metabolic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…MTX exists in the body in the form of origins and metabolites, including MTX, 7‐OH MTX, polyglutamated MTX (PGMTX), and 2,4‐diamino‐N10‐methylmorphoic acid (DAMPA) 54,55 . Recently, PGMTX and 7‐OH MTX have been found to be associated with anti‐proliferative activity and adverse reactions 54,56–58 .…”
Section: Resultsmentioning
confidence: 99%
“…MTX exists in the body in the form of origins and metabolites, including MTX, 7-OH MTX, polyglutamated MTX (PGMTX), and 2,4diamino-N10-methylmorphoic acid (DAMPA). 54,55 Recently, PGMTX and 7-OH MTX have been found to be associated with antiproliferative activity and adverse reactions. 54,[56][57][58] The HPLC and HPLC-MS/MS methods can distinguish and detect both MTX and its metabolites, but the cost is high and the sample processing is complicated.…”
Section: Rationalementioning
confidence: 99%
“…32 One study demonstrated that polymorphism in folylpolyglutamate synthase, viz., FPGS rs35789560, was associated with increased risk of relapse and decreased levels of long-chain MTX polyglutamates in a genome-wide association study. 33 Another study showed that polymorphism in gammaglutamyl hydrolase, viz., GGH rs3758149, was significantly associated with the risk of relapse of ALL in a Mexican population. 34 In the present study, we did not find any association between polymorphisms in MTRR and the risk of relapse of ALL.…”
Section: Discussionmentioning
confidence: 99%